Problems of Education and Preparation of Human Resources for Print and Publish Complex in the Conditions of the Central European Region (Global Journal of Management and Business Research, 2017)
Labor market development in the printing industry reflects the errors that have occurred in education in 90´s of the last century. The education system based on the needs of print and publish complex, where students are bound by contract with a future employer is liberalized. Employers stopped promoting education, headquarters of industry disappeared, the Ministry was reoriented to knowledge-based society, where school leaving examination should be fully accessible and preparation of blue collar workers ceased to be attractive. So called, informative values were not required and the breakdown in education, which occurred in its whole nature manifested after twenty years. Centralized nationwide education in Bratislava started to have problems. Meantime the functioning system of education, providing qualified workforce began to shake in its existence. Dominant printing company in Slovakia prefers local education at the nearest high school, with students without any long-term perspective, backgrounds or insufficient educational qualifications.
Keywords: system of education; providing qualified workforce began to shake in its existence